Methods of comparative assessment of the duration of instrumental monitoring of landslide-prone areas - Hryhorovskyi, P. Ye.; Basanskyi, V. A.; Kroshka, Yu. V.; Osadcha, I. V. (Ways to Improve Construction Efficiency, 2020)
To predict the dynamics of landslide processes, it is necessary to have information about the change of factors of man-made and natural influences over time. An important source of such information is instrumental and geodetic monitoring. To choose an effective method and systems of instrumental monitoring, it is necessary to compare the main organizational and technological indicators (duration and labor costs) of variants of such systems. The calculation of the duration and labor costs for measuring work when observing the deformations of landslides can be determined on the basis of existing norms of uniform time norms and prices for survey work or using the trace element method of normalization of labor processes. The article presents a brief analysis of the relationship between the norm of duration of measuring works, on the example of geometric leveling of class II to determine the deposition of deformation control points (marks), determined by the current uniform norms of time and rates for survey work and the duration of the same labor process. microelement method of rationing. The list and structure of works on performance of leveling of the II class, as set of elementary labor actions (operations) so isolated and outlined that the further division is inexpedient is defined. The microelements of the labor process are singled out and their normative duration in hours is determined, obtained on the basis of the experience of operation of measuring instruments during the performance of works on determination of deposition of deformation marks. The coefficient of interrelation between the existing current norms and the actual duration of the labor process, determined by the microelement rationing method for works on geometric leveling of the II class, which allows to distinguish the actual duration of the labor process as a norm, without taking into account the duration of preparatory on holiday. The inconsistency of the current standards of measurement work with modern methods of work, equipment, features of instrumental monitoring, monitoring in compacted buildings and other types of work creates the need to determine the elements of the relationship between existing standards and the actual duration of work in modern construction.